2021
DOI: 10.22146/ipas.57472
|View full text |Cite
|
Sign up to set email alerts
|

Tuber yield, morphology, and chemical properties variability of sweet cassava germplasm

Abstract: In Indonesia, the superior sweet cassava varieties are still limited due to the situation on which the majority of the superior varieties -bitter varieties- are used as industrial raw material until now. Therefore the availability of new high yielding of sweet cassava varieties is still needed. Assembling varieties requires the support of germplasm that has identified its superiority. The research objective was to evaluate tuber yield, morphology, and physico-chemical properties of cassava tuber from sweet cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In 15 accessions, physicochemical analysis of fresh tubers was performed, and the results showed that the average HCN content was 9.40 ppm and water content was 59.5%, while the starch and amylase levels were 28.8% (wb) and 11.0% (wb), respectively. In bitter cassava, the HCN content and water content were relatively higher, namely 82.88 ppm and 74.8%, respectively, while the starch and amylose contents were relatively lower, namely 15.8% (wb) and 5.5% (wb), respectively [41].…”
Section: Germplasm Evaluation In Indonesiamentioning
confidence: 93%
See 1 more Smart Citation
“…In 15 accessions, physicochemical analysis of fresh tubers was performed, and the results showed that the average HCN content was 9.40 ppm and water content was 59.5%, while the starch and amylase levels were 28.8% (wb) and 11.0% (wb), respectively. In bitter cassava, the HCN content and water content were relatively higher, namely 82.88 ppm and 74.8%, respectively, while the starch and amylose contents were relatively lower, namely 15.8% (wb) and 5.5% (wb), respectively [41].…”
Section: Germplasm Evaluation In Indonesiamentioning
confidence: 93%
“…An evaluation carried out on 75 accessions of cassava germplasms with good taste obtained data that showed that 10 accessions had high yield potential, with yields of fresh tubers ranging from 36.61 tons•ha −1 to 61.64 tons•ha −1 [41]. In 15 accessions, physicochemical analysis of fresh tubers was performed, and the results showed that the average HCN content was 9.40 ppm and water content was 59.5%, while the starch and amylase levels were 28.8% (wb) and 11.0% (wb), respectively.…”
Section: Germplasm Evaluation In Indonesiamentioning
confidence: 99%